Molecular systematics and genital morphology of the Neotropical cockroaches from the genus Xestoblatta (Blattellidae) - Vélez-Bravo, Andrés; Daza, Juan M. (Zootaxa, 2021)
The Neotropics harbors a tremendous diversity of cockroaches yet their evolutionary history is largely unknown. We reconstructed for the first time the phylogeny of the Neotropical genus Xestoblatta Hebard using mitochondrial and nuclear genes from 12 species distributed in Central America and northern South America. Additionally, we conducted a morphological analysis of external characters and male genitalia. In the phylogenetic analysis we recovered the genus Xestoblatta as non-monophyletic, resulting in three unrelated lineages. From the morphological variability described here, we identified three different morphological groups matching the phylogenetic results. The phylogenetic relationships of the three lineages within the Blattellidae were partially resolved. Lineage 1 was nested within a supported clade corresponding to the tribes Blattellini + Symplocini, while lineages 2 and 3 nested within the clade corresponding to the tribe Pseudomopini. Based on our results, we propose to divide Xestoblatta (sensu lato) into three monophyletic genera: Antroxestoblatta gen.n., Sinatablatta gen.n., and Xestoblatta (sensu stricto). We also describe a new species Sinatablatta magdalenensis sp.n. and propose a taxonomic rearrangement for Xestoblatta (sensu lato).